Promoting Science in Secondary School Education. Issue 6 (June 2017) - Chiovitti, Anthony; Duncan, Jacinta C.; Jabbar, Abdul
Abstract : Engaging secondary school students with science education is crucial for a society that demands a high level of scientific literacy in order to deal with the economic and social challenges of the 21st century. Here we present how parasitology could be used to engage and promote science in secondary school students under the auspice of a 'Specialist Centre' model for science education.